Annual Cambial Rhythm in Pinus halepensis and Pinus sylvestris as Indicator for Climate Adaptation - Prislan, Peter; Gričar, Jožica; de Luis, Martin; Novak, Klemen; Martinez del Castillo, Edurne; Schmitt, Uwe; Koch, Gerald; Štrus, Jasna; Mrak, Polona; Žnidarič, Magda T.; Čufar, Katarina. (Frontiers in Plant Science, 2016)
To understand better the adaptation strategies of intra-annual radial growth in Pinus halepensis and Pinus sylvestris to local environmental conditions, we examined the seasonal rhythm of cambial activity and cell differentiation at tissue and cellular levels. Two contrasting sites differing in temperature and amount of precipitation were selected for each species, one typical for their growth and the other represented border climatic conditions, where the two species coexisted. Mature P. halepensis trees from Mediterranean (Spain) and sub-Mediterranean (Slovenia) sites, and P. sylvestris from sub-Mediterranean (Slovenia) and temperate (Slovenia) sites were selected. Repeated sampling was performed throughout the year and samples were prepared for examination with light and transmission electron microscopes. We hypothesized that cambial rhythm in trees growing at the sub-Mediterranean site where the two species co-exist will be similar as at typical sites for their growth. Cambium in P. halepensis at the Mediterranean site was active throughout the year and was never truly dormant, whereas at the sub-Mediterranean site it appeared to be dormant during the winter months. In contrast, cambium in P. sylvestris was clearly dormant at both sub-Mediterranean and temperate sites, although the dormant period seemed to be significantly longer at the temperate site. Thus, the hypothesis was only partly confirmed. Different cambial and cell differentiation rhythms of the two species at the site where both species co-exist and typical sites for their growth indicate their high but different adaptation strategies in terms of adjustment of radial growth to environmental heterogeneity, crucial for long-term tree performance and survival.